A construção do erro trágico na arquitetura do romance Dom Casmurro de Machado de Assis - Riukstein, Rosemeri Aparecida (2007)
This dissertation intends to interpret the doubt, from the classic conception to the modern one, starting from their structural function in DOM CASMURRO narrative. The aesthetic elements, that interact in its architecture, are the metaphor and the irony, procedures that help to build the tragic error of the character-narrator Bentinho and his existencial vision in the intrigue od stubbornness. The theoretical grounding departs from the Poetics of Aristotle and extends to the modern theoreticians: Schopenhauer (1966), Kierkegaar (2005), Bergson (1983), Paz (2005) , et al. The research object is the evidence of the error caused by the doubt on the poetic effect in the romance´s architecture. The tragic error, affects ironically the whole through the optics of the narrator-author Casmurro, preparing the modern vision of Machado de Assis romance. The first chapter entitled The construction of the tragic error presents Aristotle s classic conception proceeded by the modern conception of different authors, making the correlation of the metaphor and irony with Casmurro doubt construction. The second chapter, under the title Tradition x Modernity , treats the concept of Greek tragedy and the tragic element and its function in breaking the values of the past. The third chapter entitled The double function of the tragic error treats the Aristotelian catharsis and its aesthetic effect given the tragicalness of life. In the final considerations, we refer about the effects generated by the cathartic tragicalness process through the metaphor on the dissimulation of the look of Casmurro, due to the construction of the tragic error in the architecture of the romance DOM CASMURRO of Machado de Assis